Effects of a SiO2 sub-supporting layer on the structure of a Al2O3 supporting layer, formation of Fe catalyst particles, and growth of carbon nanotube forests. Issue 72 (19th July 2016) - Lee, Jaegeun; Lee, Cheol Hun; Park, Junbeom; Lee, Dong-Myeong; Lee, Kun-Hong; Jo, Sae Byeok; Cho, Kilwon; Maruyama, Benji; Kim, Seung Min
Abstract : We investigate the effects of a SiO2 sub-supporting layer on the growth of carbon nanotube (CNT) forests, especially on the spinnability of the CNT forest into a CNT yarn, which is one of the most promising application areas. Abstract : We investigate the effects of a SiO2 sub-supporting layer on the growth of carbon nanotube (CNT) forests, especially on the spinnability of the CNT forest into a CNT yarn, which is one of the most promising application areas based on CNTs as a light-weight, strong, and electrically and thermally conductive macro-scale material. So far, most spinnable CNT forest growths have been performed using Fe/Al2 O3 deposited on a Si wafer with a thermally grown SiO2 layer. However, only a few studies have focused on examining the effects of the SiO2 sub-supporting layer on the growth and spinnability of CNT forests by microscopic analyses. Herein, using atomic force microscopy (AFM), transmission electron microscopy (TEM), liquid contact angle, and ellipsometry measurements, we demonstrate that the presence of a SiO2 sub-supporting layer significantly affects the structure of Al2 O3, adhesion between Al2 O3 and Fe layers, and the number density of Fe catalyst particles, thereby strongly affecting the growth and spinnability of CNT forests. This study opens up new possibilities for accurately controlling the growth of CNT forests by proper designing of the sub-supporting layers.